Sarcopenia, Cerebral Palsy, and Botulinum Toxin Type A. Issue 8 (August 2019) - Multani, Iqbal; Manji, Jamil; Tang, Min Jia; Herzog, Walter; Howard, Jason J.; Graham, H. Kerr
Abstract : Sarcopenia is common in both the elderly and children with cerebral palsy. Children with cerebral palsy have muscles that are much smaller than muscles in typically developing peers. Injections of botulinum toxin type A (BoNT-A) result in acute muscle atrophy in animal models and in human subjects. It is not known when or if muscles recover fully after injection of BoNT-A. These findings have implications for management protocols.